A measurement of the transverse polarization of Lambda-hyperons produced in inelastic pN-reactions at 450 GeV proton energy - Fanti, V; Lai, A; Musa, L; Nappi, A; Setzu, MG; Moore, R; Munday, D; Parker, M; Takach, S; White, T; Barr, G; Bocquet, G; et al. (1999)
A study of the polarization of Λ hyperons produced in inelastic pN reactions induced by the 450 GeV proton beam from the CERN SPS has been performed with the NA48 detector. The Λ hyperons were detected at a fixed angle of 4.2 mrad in the momentum range from 50 GeV/c to 200 GeV/c. The polarization changes from -0.053 ± 0.034 to -0.298 ± 0.074 for a transverse momentum range of the Λ between 0.28 GeV/c and 0.86 GeV/c. The Λ̄ polarization is consistent with zero.